Vibration Analysis and Control in Mechanical Structures and Wind Energy Conversion Systems - Beltran-Carbajal, Francisco (IntechOpen, 2018)
This book focuses on recent and innovative methods on vibration analysis, system identification, and diverse control design methods for both wind energy conversion systems and vibrating systems. Advances on both theoretical and experimental studies about analysis and control of oscillating systems in several engineering disciplines are discussed. Various control devices are synthesized and implemented for vibration attenuation tasks. The book is addressed to researchers and practitioners on the subject, as well as undergraduate and postgraduate students and other experts and newcomers seeking more information about the state of the art, new challenges, innovative solutions, and new trends and developments in these areas. The six chapters of the book cover a wide range of interesting issues related to modeling, vibration control, parameter identification, active vehicle suspensions, tuned vibration absorbers, electronically controlled wind energy conversion systems, and other relevant case studies.